High milk consumption does not affect prostate tumor progression in two mouse models of benign and neoplastic lesions. - Sophie Bernichtein; Natascha Pigat; Thierry Capiod; Florence Boutillon; Virginie Verkarre; Philippe Camparo; Mélanie Viltard; Arnaud Méjean; Stéphane Oudard; Jean-Claude Souberbielle; Gérard Friedlander; Vincent Goffin (PLoS ONE, 2015)
Epidemiological studies that have investigated whether dairy (mainly milk) diets are associated with prostate cancer risk have led to controversial conclusions. In addition, no existing study clearly evaluated the effects of dairy/milk diets on prostate tumor progression, which is clinically highly relevant in view of the millions of men presenting with prostate pathologies worldwide, including benign prostate hyperplasia (BPH) or high-grade prostatic intraepithelial neoplasia (HGPIN). We report here a unique interventional animal study to address this issue. We used two mouse models of fully penetrant genetically-induced prostate tumorigenesis that were investigated at the stages of benign hyperplasia (probasin-Prl mice, Pb-Prl) or pre-cancerous PIN lesions (KIMAP mice). Mice were fed high milk diets (skim or whole) for 15 to 27 weeks of time depending on the kinetics of prostate tumor development in each model. Prostate tumor progression was assessed by tissue histopathology examination, epithelial proliferation, stromal inflammation and fibrosis, tumor invasiveness potency and expression of various tumor markers relevant for each model (c-Fes, Gprc6a, activated Stat5 and p63). Our results show that high milk consumption (either skim or whole) did not promote progression of existing prostate tumors when assessed at early stages of tumorigenesis (hyperplasia and neoplasia). For some parameters, and depending on milk type, milk regimen could even exhibit slight protective effects towards prostate tumor progression by decreasing the expression of tumor-related markers like Ki-67 and Gprc6a. In conclusion, our study suggests that regular milk consumption should not be considered detrimental for patients presenting with early-stage prostate tumors.